Catalytic alkylation of unactivated C(sp3)–H bonds for C(sp3)–C(sp3) bond formation. (12th August 2019) - Chen, Zhen; Rong, Meng-Yu; Nie, Jing; Zhu, Xue-Feng; Shi, Bing-Feng; Ma, Jun-An
Abstract : This review summarizes recent advancements in catalytic direct transformation of unactivated C(sp 3 )–H bonds into C(sp 3 )–C(sp 3 ) bonds. Abstract : The construction of carbon–carbon bonds is a central tenet of modern synthetic chemistry. Metal-catalyzed C–H functionalization can serve as a particularly powerful tool for achieving carbon–carbon bond formation. This review summarizes the early adventures and recent advancements in catalytic transformation of unactivated C(sp 3 )–H bonds into C(sp 3 )–C(sp 3 ) bonds. To date, three main strategies have emerged to enable this transformation, namely, metallocarbene-triggered C(sp 3 )–H alkylation, auxiliary-directed C(sp 3 )–H alkylation, and photo-induced C(sp 3 )–H alkylation. Compared with traditional cross-coupling reactions having both coupling partners activated with functional groups or base-promoted enolate chemistry, catalytic alkylation of unactivated C(sp 3 )–H bonds for C(sp 3 )–C(sp 3 ) bond formation not only offers novel disconnections in retrosynthetic analysis, but also represents the future trend in green and atom-economic chemistry.